2017
DOI: 10.15199/48.2017.01.39
|View full text |Cite
|
Sign up to set email alerts
|

The impact of electromagnetic fields with frequency of 50 Hz on metabolic activity of cells in vitro

Abstract: The article presents the results of research on the influence of the sinusoidal electromagnetic field with a frequency of 50 Hz on the metabolic activity of two cell lines normal BJ and cancer 143b, with different exposure times (0.5 h, 1 h, 2 h and 3 h). It is shown the difference in its effect on cancer and physiological line. In order to analyze the viability there was performed the MTT test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The amount of heat depends on the characteristics of the applied field and the nature and size of the nanoparticles [37]. Many in vitro and in vivo studies, which examined the process, have confirmed the hypothesis [30][31][32]. The studies have shown that heat and EMF have a strong synergis-tic impact on the death of tumor cells [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of heat depends on the characteristics of the applied field and the nature and size of the nanoparticles [37]. Many in vitro and in vivo studies, which examined the process, have confirmed the hypothesis [30][31][32]. The studies have shown that heat and EMF have a strong synergis-tic impact on the death of tumor cells [34].…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was reported that EMF can increase the concentration of free radicals through the Fenton reaction , which damaged biomolecules such as the DNA and induced cell death [28,29]. In fenton reaction hydroxyl radical is produced from hydrogen peroxide in the presence of ferrous iron: Another study showed that EMF at a 2-mT intensity and 50 Hz frequency increased intracellular cAMP and inhibited cell proliferation [30]. Another report showed that a 50-Hz EMF reduced the antioxidant defense system significantly in the mouse brain [31].…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al have investigated that human promyelocytic leukaemia cells exposed to a 900 MHz radiofrequency field would damage mitochondrial DNA by generating reactive oxygen species pathway [7]. Koziorowska et al report a significantly different viability decrease in the cancer line compared with the increase of viability of the normal cells at different EMF exposure times [8]. The influence of EMF on cellular mechanisms is observed both inside and outside the cell.…”
Section: Introductionmentioning
confidence: 99%
“…The reagent stains dead cells in blue, but does not penetrate into viable cells, so they remain unstained because the cell membrane remains a barrier. This method has been described in the paper [3].…”
mentioning
confidence: 99%